Discrimination and Calibration of the Veterans Aging Cohort Study Index 2.0 for Predicting Mortality Among People With Human Immunodeficiency Virus in North America . (5th October 2021) - McGinnis, Kathleen A; Justice, Amy C; Moore, Richard D; Silverberg, Michael J; Althoff, Keri N; Karris, Maile; Lima, Viviane D; Crane, Heidi M; Horberg, Michael A; Klein, Marina B; Gange, Stephen J; Gebo, Kelly A; et al.
Abstract: Background: The updated Veterans Aging Cohort Study (VACS) Index 2.0 combines general and human immunodeficiency virus (HIV)–specific biomarkers to generate a continuous score that accurately discriminates risk of mortality in diverse cohorts of persons with HIV (PWH), but a score alone is difficult to interpret. Using data from the North American AIDS Cohort Collaboration (NA-ACCORD), we translate VACS Index 2.0 scores into validated probability estimates of mortality. Methods: Because complete mortality ascertainment is essential for accurate calibration, we restricted analyses to cohorts with mortality from the National Death Index or equivalent sources. VACS Index 2.0 components were ascertained from October 1999 to April 2018. Mortality was observed up to March 2019. Calibration curves compared predicted (estimated by fitting a gamma model to the score) to observed mortality overall and within subgroups: cohort (VACS/NA-ACCORD subset), sex, age <50 or ≥ 50 years, race/ethnicity, HIV-1 RNA ≤ 500 or >500 copies/mL, CD4 count <350 or ≥350 cells/µL, and years 1999–2009 or 2010–2018. Because mortality rates have decreased over time, the final model was limited to 2010–2018. Results: Among 37230 PWH in VACS and 8061 PWH in the NA-ACCORD subset, median age was 53 and 44 years; 3% and 19% were women; and 48% and 39% were black. Discrimination in NA-ACCORD (C-statistic = 0.842 [95% confidence interval CI, .830–.854]) was better than in VACS (C-statistic = 0.813 [95% CI, .809–.817]). Predicted and observed mortality largely overlapped in VACS and the NA-ACCORD subset, overall and within subgroups. Conclusions: Based on this validation, VACS Index 2.0 can reliably estimate probability of all-cause mortality, at various follow-up times, among PWH in North America. Abstract : Based on calibration curves that compared VACS Index 2.0 predicted mortality to observed mortality, overall and within important subgroups, the VACS Index 2.0 can reliably estimate probability of all-cause mortality over time among people with HIV in North America.